Conservatively managed tibial shaft fractures in Nottingham, UK: are pain, osteoarthritis, and disability long-term complications?. Issue 6 (December 1997) - Greenwood, D C; Muir, K R; Doherty, M; Milner, S A; Stevens, M; Davis, T R
Abstract : OBJECTIVES: To investigate longterm pain and disability subsequent to a tibial shaft fracture treated conservatively. DESIGN AND SETTING: Subjects who had sustained a tibial shaft fracture more than 27 years ago were compared with those who had not. SUBJECTS: 572 fracture patients (identified from the records of the plaster room) aged over 16 at the time of injury were contracted and were compared with 2285 randomly selected subjects matched for age, sex, and general practice. MAIN OUTCOME MEASURES: Self reported knee pain; self reported GP's diagnosis of osteoarthritis; ability to climb stairs, walk 100 yards, to bend, kneel, or stoop; and SF-36 physical functioning score. RESULTS: Subjects were reviewed between 27 and 41 years after tibial shaft fracture (mean 35 years). Fracture patients were more likely to suffer chronic knee pain (odds ratio 1.23; 95% confidence interval (CI) 1.00, 1.51) and report being given a diagnosis of osteoarthritis by their GP (odds ratio 1.46; 95% CI 1.08, 1.97). The ability to climb stairs, walk 100 yards, and bend, kneel, or stoop was less in the fracture group than the other subjects. The SF-36 physical function score was significantly lower in the fracture group. CONCLUSIONS: More than 27 years after a tibial shaft fracture, subjects have more knee pain than the rest of the population. They also have greater difficulty performing everyday physical activities. The excess morbidity may be due to injury factors or treatment factors, and further research is needed to investigate this important association further.